Modern state of natural landscape complexes of Zaporizhzhya area - Лисенко, Валерій Іванович; Лысенко, Валерий Иванович; Lysenko, Valerii; Чебанова, Юлія Василівна; Чебанова, Юлия Васильевна; Chebanova, Yuliia (My University, 2016)
Formation of modern landscapes of Zaporizhzhya region occurred in the Holocene period. During the Holocene wet phase changing climate fairly arid, warm - rather cold, but the average climatic indicators were close to modern. These conditions contributed to the formation of steppe zonal type of landscape. However, due to prolonged exposure to diverse steppe landscapes economic impacts associated with mismanagement of their natural potential and increasing human pressure on the natural environment has been transformed natural landscapes and change their properties. The result of this action was that the area landscapes drastically reduced. Zaporizhzhya region was the most economically mastered in all regions of Ukraine. To further study the issues to optimize environmental management of the region, the article reproduced a modern structure of landscapes area. The area characterized Zaporizhzhya region lowland class and type steppe landscapes. Three subtypes of landscapes: the north, middle and dry steppe. Each subtype is divided into land. Within North steppe subtype isolated Dniester-Dnieper and the Left-Bank Dnepr-Azov province. Medium steppe subtype is represented by the Black Sea margin, and dry steppe - Black sea-Azov. The most popular items on the optimization of environmental management are landscaped areas and areas of morphological units within them. That level reflects the nature of the landscape area inside the area landscape differentiation. Within the Zaporizhzhya region allocated 7 landscaped areas: highland Azov, highland- Dnieper south slope, Kinsko-Yalinska low-lying, low- lying Azov, the Dnieper-Molochansk low-lying, Western Azov-slope highland and lowland Prisivasko- Priazov.
Keywords: landscape structure; conomic use of natural landscapes; Zaporizhzhya area; steppe; landscape areas; soil; optimization of nature use